2023
DOI: 10.1021/acsanm.2c05389
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Metal–Organic Framework Nanochannels for Water Transport and Purification

Abstract: Artificial water nanochannels (AWCs) have drawn great attention due to their potential use in water purification. Herein, we propose an AWC design, which is based on coordinatively functionalizing unsaturated metal sites found in metal−organic frameworks (MOFs) with one-dimensional nanochannels. As a computational demonstration, we consider two MOFs, namely, Ni-CPO-27 and Ni-CPO-54, and graft proline, imidazolecarboxylic acid, imidazolecarboxaldehyde, pyrazolecarboxylic acid, and pyrazole carbaldehyde molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Having established that Mg2(dobdc) strongly and reversibly adsorbs H2S and is nontoxic to human cells at therapeutic concentrations, we explored whether alternative stimuli to vacuum could trigger H2S desorption from Mg2(dobdc) under more biologically relevant conditions. Given the strong binding of water in open metal site MOFs, 91 it is likely that water is capable of facilitating H2S release from the framework. To test this hypothesis, a known amount of H2S-dosed Mg2(dobdc) was suspended in a stirring solution of HEPES buffer (pH 7.4) (SI section 6).…”
Section: Resultsmentioning
confidence: 99%
“…Having established that Mg2(dobdc) strongly and reversibly adsorbs H2S and is nontoxic to human cells at therapeutic concentrations, we explored whether alternative stimuli to vacuum could trigger H2S desorption from Mg2(dobdc) under more biologically relevant conditions. Given the strong binding of water in open metal site MOFs, 91 it is likely that water is capable of facilitating H2S release from the framework. To test this hypothesis, a known amount of H2S-dosed Mg2(dobdc) was suspended in a stirring solution of HEPES buffer (pH 7.4) (SI section 6).…”
Section: Resultsmentioning
confidence: 99%
“…Since the Ni atom contains unpaired electrons, all calculations were spin-polarized . As we demonstrated in our previous work, the ground state of Ni-CPO-27 was achieved when the initial spin state of the Ni atom was set to 2 …”
Section: Methodsmentioning
confidence: 99%
“…Using molecular simulations, we recently studied water diffusion in Ni-CPO-27 and Ni-CPO-54 MOFs, whose onedimensional pores were functionalized by grafting imidazolecarboxaldehyde/pyrazolecarboxaldehydes, zwitterionic imidazolecarboxylic acids, pyrazolecarboxylic acids, and proline on to the coordinatively unsaturated open metal sites. 27 This type of coordination bond found in the proposed AWCs (i.e., coordination of −COO− on to an open metal site) was experimentally demonstrated in Zn-CPO-27 with zwitterionic proline. 28 We found that the proline-grafted Ni-CPO-54 (proline-Ni-CPO-54) had the largest self-diffusion coefficient among the structures that were investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic framework (MOF) is an extraordinary class of materials that potentially revolutionizes water purification technology. MOFs are known for their unique structure and exceptional adsorption capabilities, which emerged as a beacon in the need for clean and accessible water for drinking and domestic applications. Additionally, MOF possesses exceptional reusability features by desorbing the adsorbed pollutant using simple solvent washing, demonstrating their superior advantage in reducing water purification costs and associated waste generation in comparison with many conventional adsorbents .…”
Section: Introductionmentioning
confidence: 99%